3D human tissue models and microphysiological systems for HIV and related comorbidities - Yin, Dwight E.; Palin, Amy C.; Lombo, Tania B.; Mahon, Robert N.; Poon, Betty; Wu, Da-Yu; Atala, Anthony; Brooks, Kristina M.; Chen, Shuibing; Coyne, Carolyn B.; D’Souza, M. Patricia; Fackler, Oliver Till; et al. (Trends in biotechnology, 2024)
Three-dimensional (3D) human tissue models/microphysiological systems (e.g., organs-on-chips, organoids, and tissue explants) model HIV and related comorbidities and have potential to address critical questions, including characterization of viral reservoirs, insufficient innate and adaptive immune responses, biomarker discovery and evaluation, medical complexity with comorbidities (e.g., tuberculosis and SARS-CoV-2), and protection and transmission during pregnancy and birth. Composed of multiple primary or stem cell-derived cell types organized in a dedicated 3D space, these systems hold unique promise for better reproducing human physiology, advancing therapeutic development, and bridging the human-animal model translational gap. Here, we discuss the promises and achievements with 3D human tissue models in HIV and comorbidity research, along with remaining barriers with respect to cell biology, virology, immunology, and regulatory issues.
Online verfügbar 8 December 2023, Version des Artikels 1 May 2024
Gesehen am 24.01.2025